Implementing Academic Supervision to Improve Teacher Professionalism in the Independent Curriculum - Atika Huril'in; Fahri Muhaimin Fabrori Fabrori (Laskar Karya, 2026)
The Indonesian government has taken strategic steps to improve the quality of education, with an emphasis on improving the quality of educators and education personnel who play a crucial role in the education system. This effort includes developing teacher professionalism and competence. This study aims to examine the extent to which the implementation of academic supervision has improved teacher professionalism in the Merdeka Curriculum. This research was conducted using qualitative descriptive research utilizing literature studies. The descriptive research method is an approach that aims to provide an overview of various possible solutions to address current problems. The research results show that effective and continuous academic supervision can improve teacher professionalism and support the optimal implementation of the Independent Curriculum. The impact of academic supervision is evident in improved teacher competency in lesson planning, changes in teaching practices to be more innovative and student-centered, and teachers' ability to carry out learning assessments more systematically. Furthermore, the implementation of the Independent Curriculum also encourages the creation of a more enjoyable and participatory learning environment for teachers, students, and parents, as schools are given the flexibility to develop learning according to the needs and characteristics of students. Thus, academic supervision plays a crucial role as a means of developing teacher professionalism in supporting improvements in the quality of learning